Pengaruh Modal dan Tenaga Kerja Terhadap Peningkatan Produksi Pada Usaha Mebel Mulyo Joyo Aimas di Kabupaten Sorong - Pasaribu, Sandi H. (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out how capital and labor influence furniture production in the Mulyo Joyo furniture business. This research is quantitative descriptive in nature, the analytical tool used is multiple linear regression, where the results of the research show that simultaneously capital and labor and increase, this increases the amount of furniture production. From this research, information was obtained relating to the total revenue and profits obtained by the furniture business. When compared with the total revenue and profit in 2020, the total revenue and profit from the furniture business has decreased because production in 2020 decreased.